Job's Death, the Death of Hope Irony and Allusions in Job 17, 11-16 - Beyer, Andrea (Biblische Notizen, 2024)
This contribution offers an analysis of Job 17, 11-16, a text that stands in the context of the opening lament (Job 3) and the ambivalence of the desire to die and the longing for life in Job. A comparison with Ps 27 reveals the functions of allusions and ironic refractions in the treatment of the themes of hope and death in Job 17, 11-16. The relationship between the book of Job and tradition is not purely critical, but constructive, as allusions create irony, correction, contradiction and gaps that readers can fill in.
CRIS-Team Scopus Importer:2024-11-22